microRNA signature for human pancreatic cancer invasion and metastasis - CHENG, HE (D.A. Spandidos, 2012)
Pancreatic cancer has the poorest prognosis among all human malignant solid tumors, mainly due to its high invasive and metastatic biological features. microRNAs (miRNAs) are a group of endogenous and small non-coding RNA molecules 18–25 nucleotides in length, functioning as either tumor-suppressor genes or oncogenes. Evidence has shown that regulation of miRNAs in pancreatic cancer is associated with tumor growth, invasion, metastasis and resistance to therapy. Over the last decade, many studies have also found that there is a close relationship between miRNAs and biological characteristics of pancreatic cancer invasion and metastasis, such as the presence of cancer stem cells, epithelial-mesenchymal transition (EMT) phenotype, DNA methylation or epigenetic alteration, and the activation of some specific signaling pathways. Therefore, better understanding of the complex role of miRNAs in the development and progression of pancreatic cancer metastasis may provide new insights that could be of therapeutic consequence. In this brief review, we discuss the literature concerning the correlation between miRNAs and pancreatic cancer, focusing on miRNAs that contribute to pancreatic cancer invasion and metastasis, particularly on cancer stem cell characteristics, the EMT process, epigenetic modifications and tumor-associated signaling pathways.